Meningkatkan Pola Berpikir Kritis dengan Peran Epistemologi Filsafat di SD Negeri 2 Sumber Harum - Karno, Budi Puspito; Susanti, Rahmi; Yosef, Yosef; Nawawi, Effendi (Asian Journal of Early Childhood and Elementary Education, 2024)
Primary education has a very significant role in forming the foundation of a critical mindset in children. At this stage, students should begin to be taught how to understand information in depth, make informed judgments, and develop the ability to make decisions based on logical reasoning. This research aims to develop the critical thinking patterns of students at SD Negeri 2 Sumber Harum through the application of philosophical epistemology in learning. This study uses a qualitative approach with a descriptive design to explore the application of philosophical epistemology in learning to improve the critical thinking of students at SD Negeri 2 Sumber Harum. The results of this study show that the application of philosophical epistemology in learning at SD Negeri 2 Sumber Harum significantly improves students' critical thinking skills. Through learning methods such as group discussions, debates, and case studies, students not only understand the subject matter more deeply, but are also able to analyze, evaluate, and construct logical arguments. This improvement was seen in the results of the critical thinking test, which showed an increase in the average score from 58 to 76 after the intervention. In addition, students also began to show higher confidence in expressing opinions and being actively involved in the learning process.